Accounting Treatment for Unrestricted Investment Deposits and its Implication to Islamic Financial Institution - M. Ghafur Wibowo; Joko Setyono; Kurnia Rahman Abadi (Global Review of Islamic Economics and Business, 2013)
The objective of this paper is to analyze the accounting treatment for mudharabah especially for account unrestricted investment (mudharabah mutlaqoh) in practical side which has been appling in the current Islamic banking system. This paper also concerns on the impliaction of different accounting treatment to the islamic financial institution. This study finds that there two different accounting treatment for Unrestricted Mudharabah currently practised by Islamic banking, namely as liability and as different account between equity and liability. The two differents of accounting treatment for mudharabah investment account (UIAHS) will have some implication to Islamic banking, namely: Profit distribution, Capital Adequacy Ratio (CAR), Risk management and Capital structure. Based on IFSB Capital Adequacy Standard, in accounting treatment AAOFI standard, since the mudharabah Investment account has portion between liability and equity, thus the alpha maybe equal to 0.5. However, in case of Malaysia which is more based on IFRS which is treated this account as a liability, alpha is close to one (1). The different CAR also will have implication on the risk management that should be conducted by Islamic bank. Capital structure policy is another aspect that will be influenced by the different of accounting treatment of UIAHS. Hence, the accounting treatment of UIAHS on whether it will be treated as equity or liability will has direct effect on capital structure policy and some other aspect such as default risk, bankruptcy cost etc.